2007
DOI: 10.1007/s10336-007-0192-7
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the blue tit (Parus teneriffae-group) on the Canary Islands based on mitochondrial DNA sequence data and morphometrics

Abstract: An analysis of the sequences of the mitochondrial cytochrome b gene (1005 bp) of the Parus teneriffaegroup from the Canary Islands and North Africa revealed new insights into the phylogeography of this taxon. The origin of the radiation on the Canarian Archipelago was apparently one of the central islands-Tenerife or Gran Canaria. The populations on El Hierro (P. t. ombriosus) and La Palma (P. t. palmensis) represent distinct monophyletic lineages. Blue tits from Gran Canaria are genetically distinct from thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 40 publications
2
38
0
1
Order By: Relevance
“…Possibly due to recent colonizations of the Canary Islands, little genetic divergence compared to the African mainland have been found in taxa such as the Atlantic Canary (Serinus canaria) (Dietzen et al 2005), the Blackcap (Sylvia atricapilla) and the Sardinian Warbler (S. melanocephala) (Dietzen et al 2008a), while subspecies of Blue Tit (Parus teneriffae degener) (Kvist et al 2005), did not differ genetically from P. t. ultramarinus (Dietzen et al 2008b), and nor were there differences between subspecies of Southern Grey Shrike (Lanius meridionalis) (Gonzalez et al 2008) or Great Spotted Woodpecker (Dendrocopos major) (Garciadel-Rey et al 2007). During the last *3 My, other Canarian taxa have also followed probable multiple colonizations, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly due to recent colonizations of the Canary Islands, little genetic divergence compared to the African mainland have been found in taxa such as the Atlantic Canary (Serinus canaria) (Dietzen et al 2005), the Blackcap (Sylvia atricapilla) and the Sardinian Warbler (S. melanocephala) (Dietzen et al 2008a), while subspecies of Blue Tit (Parus teneriffae degener) (Kvist et al 2005), did not differ genetically from P. t. ultramarinus (Dietzen et al 2008b), and nor were there differences between subspecies of Southern Grey Shrike (Lanius meridionalis) (Gonzalez et al 2008) or Great Spotted Woodpecker (Dendrocopos major) (Garciadel-Rey et al 2007). During the last *3 My, other Canarian taxa have also followed probable multiple colonizations, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The subspecies ultramarinus is also found in North Africa, whereas ogliastrae occurs in Spain and caeruleus in Sweden. In Kvist et al [15], the birds on Fuerteventura and Lanzarote were separated from North Africa and put into a separate subspecies, degener , but the newer data indicate that this may not be the case [16], [17]. The subspecies categorisation of Dietzen et al [17] is shown on the map in Figure 1 .…”
Section: Methodsmentioning
confidence: 97%
“…Since we did not find evidence to distinguish L. m. koenigi from L. m. algeriensis, these two taxa may be considered as synonymous, and they together correspond to a different species. Although the evolutionary histories of different bird species differ in terms of mode and timing, low levels of genetic divergence have been found in other taxa inhabiting the Canary Islands and Africa, e.g., in Sylvia (Dietzen et al 2007b) and in subspecies of the genus Parus (Dietzen et al 2007a). However, only one sample of L. m. algeriensis was available and, due to shortage of DNA, we could only sequence the cytochrome b gene.…”
Section: Tandem Repeatsmentioning
confidence: 99%
“…In the course of recent years, numerous new endemic species of vertebrates in the Canary Islands have been described based on the utilization of molecular techniques (Delgado 2001). Recent studies applied molecular markers in closely related and morphologically very similar bird taxa and have proved to be useful tools to elucidate genetic variability and phylogenetic relationships (Garcia-del-Rey et al 2007;Päckert et al 2006;Dietzen et al 2007a).…”
Section: Introductionmentioning
confidence: 99%